Fundamental Factors and Stock Returns: Market Capitalization’s Role in Forming Investment Outcomes - Subing, Hesty Juni Tambuati; Zulfahmi, Iqbal (SAN Scientific, 2025)
Telecommunication is one type of industry that has a major influence on the smooth running of economic activities. Communication is the main activity in business activities and contributes significantly to the Indonesian economy. In Indonesia, some telecommunications companies have gone public such as PT. Telekomunikasi Indonesia Tbk, PT. Indosat Tbk, PT. XL Axiata Tbk, and PT. Smartfren Telecom Tbk. The shares of these companies have returned to their owners every year with different return values. This finding is the basis for conducting research on the four major telecommunications companies that have large capitalization values and a large market share and, have been established for a long time and are still consistent to this day. The managerial implications of this study indicate that understanding fundamental factors such as profitability, liquidity, and capital structure is very important for company management in increasing stock returns and market capitalization. By optimizing fundamental performance, companies can increase their attractiveness to investors and strengthen their market position. In addition, the role of market capitalization as a moderating variable confirms that companies with large capitalization tend to be more stable in facing market fluctuations.